Володимир Свідзінський і шістдесятники: контексти осягання проблеми - Рарицький, О. (Слово і Час, 2018)
У статті розглянуто роль та значення творчості В. Свідзінського у формуванні культурницького
коду українського шістдесятництва. Досліджено впливи художньої свідомості поета на
становлення мистецької самоідентифікації творчих особистостей, ідеться про увиразнення
індивідуального стилю, кристалізацію незалежної життєвої позиції представників покоління на
тлі ідеологічних процесів доби. Проблеми вивчення наукової біографії митця, характеристика
його поетичної творчості проілюстровані в літературознавчих студіях В. Коротича, І. Дзюби,
В. Стуса, В. Шевчука. Для шістдесятників поетичний доробок Свідзінського виявився взірцем
щодо розуміння свободи творчості, духовної суверенності особистості, самототожності. The paper evaluates the role and significance of V. Svidzinskyi’s creative work in forming the cultural
code of the Ukrainian ‘Sixtiers’ movement.
The researcher tries to show how Svidzinskyi’s artistic consciousness influenced the process of
forming creative self-identification of new authors, marked their individual style and helped to strengthen
the independent life position of the generation representatives against the background of the epoch’s
ideological processes. The issues of the artist’s biography and characteristics of his poetic activity
became the subject of the literary studies by V. Korotych, I. Dziuba, V. Stus, V. Shevchuk. For the
writers of the 1960s Svidzinskyi’s creative activity turned out to be a sample of understanding creative
freedom, inner sovereignty of personality and self-identity. The author attracted young writers with his
low-sounding but at the same time particularly expressive modern poetry, with free feelings and clarity
of poetic thinking, with authenticity of the reflected existence. The attention was also drawn by the
invariability of V. Svidzinskyi’s personality, as he was absolutely unfit for adjusting himself to the swift
changes of the epoch and steadily cultivated his non-conformism that became the reason of his tragic
death and unjust falling into oblivion. However the writers of the 1960s were influenced by Svidzinskyi’s
creative work to the great extent, when they formed and established their own manner of writing.
Under the conditions of total offensive against human personality some of them refer to Svidzinskyi’s
heritage where they find inner resources for resisting the cruel reality. It may be assumed that the
first impressions from the poetry were caused by aesthetic factors, the further ones – by the power of
the author’s inner resistance to Stalin’s epoch. The Sixtiers found Svidzinskyi’s poetry phenomenal
due to his metaphoric associative thinking, his emphatic and unique perception of world, deep
emotional sphere of his inner self-expression and self-contemplation, his exceptional sense of implicit
freedom. В статье исследуется роль и значение творчества
В. Свидзинского в формировании культурнического кода украинского
шестидесятничества. Описано влияние художественного сознания
поэта на самоидентификацию творческих личностей, речь идет
о выразительности индивидуального стиля, кристаллизации
независимой жизненной позиции представителей поколения
шестидесятников на фоне идеологических процессов эпохи.
Проблемы изучения научной биографии автора, характеристика
его поэтического творчества проиллюстрированы в
литературоведческих исследованиях В. Коротича, И. Дзюбы,
В. Стуса, В. Шевчука. Для шестидесятников поэтическое наследие
В. Свидзинского стало образцом свободы творчества, духовной
независимости личности, самоидентичности.